Formation and function of the immunological synapse. - Van Der Merwe, P (2002)
Less than five years ago it was reported that cell surface molecules at the contact site between CD4 T cells and antigen-presenting cells redistribute into distinct patterns, forming an organized interface termed the immunological synapse. More recently, similar reorganized interfaces have been observed with CD8 T cells and NK cells, suggesting that they may be a common feature of lymphocyte activation. Although there has been some advance in our understanding of the mechanisms underlying this redistribution, its purpose remains unclear and controversial.